Entrance System for High Schools: Development of the Guttman Attitude Scale towards Local Placement - Bahattin İnam; Necla Turanlı; Meltem Coşkun (Sakarya University Journal of Education)
The foundation of transition from elementary education to secondary education is rooted in exams as well as the success gained from those exams. Although students were placed into a secondary education institution based on their exam scores in the previous exam system, with the newly-implemented ‘Entrance System for High Schools’ (shortly LGS in Turkish), there are two different student placements under consideration: (1) centralized placement, and (2) local placement. The purpose of the current study is to develop an attitude scale based on Guttman Scaling in order to investigate the attitudinal behaviors of the parents in the current education system. In line with this objective, a draft scale, consisting of ten items were administered to 241 parents whose children were placed into a high school in the 2017-2018 academic year. In the direction of the responses provided by the parents, four items were removed from the scale. Reliability test was conducted on the residual six items. The coefficient of reproducibility was calculated as 0,986 and scalability coefficient was 0,925, which is considered as acceptable for the reliability of the current scale. It was concluded that Guttman Scaling for local placement (i.e., address-based placement) is a reliable research tool for measuring attitudes towards placements in secondary education.